One hundred and thirty years from the birth of a medical lieutenant colonel and academician Kosta Todorović: warrior, physician, scientist... humanist - Šuvaković, Uroš V.; Petrović, Jasmina S.; Pavlović, Milorad D. (Vojnosanitetski pregled, 2021)
130 years passed at the beginning of July 2017 from the birth of a giant of Serbian and Yugoslav medicine, the founder of Serbian infectious disease, the academician Prof. Dr. Kosta P. Todorović. We shall try to remind contemporary generations of the ethics and scientific contribution of this primarily military medical officer, the participant in the Balkan Wars and the First World War, the recipient of the Albanian Commemorative Medal and warrior at the Thessaloniki Front, then civilian physician, infectious diseases professor, the founder and the director of the Clinic for Infectious Diseases in Belgrade, an academician of the SASA and several other Yugoslav and foreign academies, the secretary of the Department of Medical Sciences of the SASA for a quarter of a century, a member of the Presidency of the SASA, a doctor of science honoris causa of the Belgrade University, an advisory member of the WHO Committee on International Issues of Quarantine, the president and later the honorary president of the Serbian Medical Society, the honorary president of the Association of Medical Societies of Yugoslavia, the founder and the president of the Association of recipients of the Albanian Commemorative Medal, a recipient of a great number of domestic and foreign medals, awards and recognitions, but above all the great humanist. Simultaneously, we shall try to indicate in this paper not only to more or less known data about this unique person in the recent history of our medicine, but also to humanitarian principles and to morals he managed and to scientific contributions that have not received an adequate attention. We shall do that by analyzing contents of some of his works, of biographic and bibliographic data, as well as by research insight into historical material relevant to the life and work of the academician Todorović, as well as into the already published papers dealing with the personality of the founder of the Serbian infectious disease.